Anti-aging aerial cable and production process thereof
By blending modified nanomagnesium oxide and mesoporous silica-loaded compounds with crosslinked polyethylene, the aging problem of crosslinked polyethylene insulating materials at high temperatures and high fields is solved, and the electrical resistance and oxidation resistance of the cable is significantly improved. , extends service life.
Patent Information
- Application Number
- CN202411406600.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-10
AI Technical Summary
Crosslinked polyethylene insulating materials are prone to space charge accumulation, local discharge and water branches under high temperature and high fields, resulting in advance breakdown of cable insulation layer, and the dispersion of nanomagnesium oxide in polyvinyl matrix is poor, affecting the overall performance of the material. .
Modified nanomagnesium oxide and mesoporous silica-supported compounds are used as branch aging agents and antioxidants. The surface properties of nanomagnesium oxide are improved through ultrasonic dispersion and chemical modification, and blended with crosslinked polyethylene to form a capable The aging resistance agent at the crosslinking site enhances the mechanical and oxidation resistance of the insulating layer.
It significantly improves the electrical resistance, mechanical properties and oxidation and aging resistance of the insulating layer, extends the service life of the cable, inhibits the initiation and growth of electric branches, and improves the overall aging performance of the cable.
Smart Images

Figure BDA0005076787690000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of cables, and in particular to an aging-resistant overhead cable and a production process thereof. Background Art
[0002] Overhead cable is a new high-voltage power transmission method between overhead wires and underground cables. It has the main characteristics of high power supply reliability, good power supply safety, convenient installation and maintenance, and reasonable economy. Overhead cables usually include overhead wires, insulation layers, and outer protective sheaths. Common insulation layer materials include cross-linked polyethylene, polyethylene, polypropylene, ethylene propylene rubber, and chloroprene rubber. Cross-linked polyethylene insulation material is a three-dimensional mesh thermosetting material. Compared with polyethylene, which is a linear thermoplastic material, its mechanical properties and thermal stability are significantly improved.
[0003] When cross-linked polyethylene insulation materials are subjected to multiple effects of factors such as temperature and electric field, the presence of impurities can easily accumulate space charges inside the sample, resulting in local discharges and the formation of electrical dendrites, which can cause the cable insulation layer to break down quickly and prematurely. Therefore, improving the electrical resistance of polymer insulation materials under high temperature and high field is the key to improving the transmission voltage level of power cables. When overhead cables are installed in high-altitude environments such as across mountains and rivers, the mechanical stress generated by operations such as bending and stretching of the cables will form tiny cracks in the internal insulation. External moisture can easily penetrate through the cracks and gather inside the insulation material to form water droplets. Under the action of the alternating electric field, water dendrites are formed, destroying the insulation layer structure and causing insulation degradation. During use, the insulation layer material of the overhead cable ages due to the effects of light, heat, and oxygen, resulting in performance degradation.
[0004] Generally, tree-resistant aging agents, water tree inhibitors and antioxidants are added to cross-linked polyethylene insulation materials to improve the aging phenomena such as electrical aging, water tree aging, light aging, heat aging, oxygen aging of cables, but the dispersion compatibility of small molecule additives in the cross-linked polyethylene matrix is poor, and it is easy to migrate and fail, and the service life of the cable cannot be effectively extended. The patent with the announcement number CN105860426B discloses a method for preparing a cable insulation material comprising nano-magnesium oxide / low-density polyethylene / modified bentonite and its application, and the prepared insulation material has high heat resistance and strength, short aging time and can be kept for a long time without degradation under high temperature and high pressure. However, the disadvantage is that the surface of nano-magnesium oxide is hydrophilic and oleophobic, and it is easy to agglomerate, and the compatibility with the polyethylene matrix is poor. Previous studies have shown that nano-magnesium oxide is of great significance for improving dielectric strength and improving the distribution of space charge, so it is necessary to improve the surface properties of nano-magnesium oxide, so that it is more evenly dispersed in the matrix, and the comprehensive performance of cross-linked polyethylene insulation materials is improved. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides an aging-resistant overhead cable and a production process thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] An aging-resistant overhead cable comprises a conductor core, an insulating layer and a sheath layer from the inside out; the conductor core is formed by twisting a plurality of aluminum alloy wires, and the sheath layer is made of a TPE sheath material; the insulating layer is made of cross-linked polyethylene, and the cross-linked polyethylene comprises the following raw materials by weight: 170-180 parts of low-density polyethylene, 10-12 parts of a cross-linking agent, 8.5-10.5 parts of a tree aging resistance agent and 4-6 parts of an antioxidant; the cross-linking agent is benzoyl peroxide;
[0008] The preparation of the aging-resistant overhead cable comprises the following steps:
[0009] Step S1: low-density polyethylene is placed in a rheometer for melt blending, mixed at 105-110° C. and a rotation speed of 50 r / min for 4-6 minutes, then an anti-tree aging agent and a cross-linking agent are added, mixed for another 3 minutes, an antioxidant is added, and finally mixed for 10-15 minutes to obtain cross-linked polyethylene;
[0010] Step S2: Twisting the aluminum alloy wires to form a conductor core, extruding and depositing the cross-linked polyethylene on the periphery of the conductor core using an extruder to form an insulating layer; then extruding and depositing the TPE sheath material on the periphery of the insulating layer to obtain a sheath layer, and annealing after extrusion to obtain an aging-resistant overhead cable.
[0011] The preparation of the anti-branching agent comprises the following steps:
[0012] Step A1: Add nano magnesium oxide to toluene, ultrasonically disperse for 40 minutes, add erucic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110-120°C, reflux and stir for 48-51 hours, then centrifuge for 10-15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain modified magnesium oxide;
[0013] Further, the dosage ratio of nano magnesium oxide, toluene, erucic acid and N,N'-dicyclohexyldiimide is 5-7g:120mL:10g:2g;
[0014] During the reaction of step A1, the hydroxyl groups on the surface of nano-magnesium oxide react with erucic acid to generate nano-magnesium oxide with unsaturated alkane long chains on the surface, i.e., modified magnesium oxide;
[0015] Step A2: Add modified magnesium oxide to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4-5 hours to obtain an epoxy product; in a nitrogen atmosphere, add 3-benzoylbenzoic acid and toluene to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8-10 hours, then heat to 110-120°C, stir for 1-2 hours to obtain a hydroxyl product;
[0016] Further, the dosage ratio of modified magnesium oxide, dichloromethane and 3-chloroperoxybenzoic acid is 12-16 g: 180-190 mL: 0.5-1.0 mol; the dosage ratio of 3-benzoylbenzoic acid, toluene, pyridine and epoxy product is 25-30 g: 100-110 mL: 0.2-0.25 mol: 13-15 g;
[0017] During the reaction of step A2, the unsaturated double bonds on the surface of the modified magnesium oxide are oxidized to epoxy groups to obtain an epoxy product; the carboxyl group of 3-benzoylbenzoic acid reacts with the epoxy group of the epoxy product to obtain a hydroxyl product;
[0018] Step A3: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add the above acryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly dropwise add the mixed solution b into the mixed solution a in a 0°C ice water bath, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain a tree aging resistant agent;
[0019] Further, the dosage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 14-16 g: 0.01-0.015 mol: 0.5-1.0 mol: 70-80 mL; the dosage ratio of acryloyl chloride and dimethyl sulfoxide is 4.5-5.4 g: 20-30 mL; the dosage ratio of the mixed solution a and the mixed solution b is 75-85 mL: 25-35 mL;
[0020] During the reaction of step A3, the hydroxyl group of the hydroxyl product reacts with acryloyl chloride to generate a dendrite aging resistance agent containing a terminal carbon-carbon double bond.
[0021] The preparation of the antioxidant comprises the following steps:
[0022] Step B1: In a nitrogen atmosphere, 5-methylthiothiophene-2-carboxaldehyde and acetic anhydride are added to a reaction bottle, refluxed and stirred, and the temperature is raised to 150-170°C, and potassium carbonate is added, and the reaction is stirred at constant temperature for 24-26 hours, and the unsaturated carboxylic acid is extracted, rotary evaporated, and dried to obtain an unsaturated carboxylic acid; the unsaturated carboxylic acid is added to DMF, stirred, and thionyl chloride is slowly added, the temperature is raised to 40-50°C, and the reaction is stirred at constant temperature for 4-5 hours, and the acyl chloride product is obtained by filtering, extracting, and drying;
[0023] Further, the usage ratio of 5-methylthiothiophene-2-carboxaldehyde, acetic anhydride, and potassium carbonate is 0.1 mol: 0.05-0.07 mol: 5-8 mmol; the usage ratio of unsaturated carboxylic acid, DMF, and dichlorothionyl is 0.1 mol: 90 mL: 0.1-0.15 mol;
[0024] During the reaction of step B1, the aldehyde group of 5-methylthiothiophene-2-carboxaldehyde reacts with acetic anhydride to generate a carboxylic acid containing a carbon-carbon double bond, i.e., an unsaturated carboxylic acid; the unsaturated carboxylic acid reacts with thionyl chloride to generate an acyl chloride product;
[0025] Step B2: Add 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1, then add the above-mentioned acyl chloride product into dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain compound s;
[0026] Further, the dosage ratio of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.01-0.015 mol: 0.1 mol: 80-90 mL; the dosage ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 100-110 mL; the dosage ratio of the mixed solution 1 and the mixed solution 2 is 85-95 mL: 105-115 mL;
[0027] During the reaction of step B2, the hydroxyl group of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol reacts with the acyl chloride of the acyl chloride product to generate a compound s containing hindered phenol, sulfide and thiophene ring structures;
[0028] Step B3: Compound S is added to acetone, and the mixture is stirred at room temperature for 10-20 minutes to obtain a mixed solution, and then carboxyl hollow mesoporous silica is added, and the mixture is stirred at room temperature for 2-2.5 hours, and then vacuumed for 30 minutes, and then allowed to flow to the atmosphere for 15 minutes. The steps of vacuuming and then passing through the atmosphere are repeated three times, and the loaded product is obtained after washing with ethanol and deionized water, drying and grinding;
[0029] Further, the usage ratio of compound S, acetone, and carboxyl hollow mesoporous silica is 43-45 g: 430-450 mL: 20-25 g;
[0030] During the reaction of step B3, under a vacuum environment, the mixed solution formed by compound s and acetone can overcome the "barrier" at the port of the carboxyl hollow mesoporous silica under the action of van der Waals force, so that compound s enters the interior of the mesoporous silica to obtain a loaded product;
[0031] Step B4: Add the loaded product to DMF, start stirring, slowly add thionyl chloride, raise the temperature to 40-50°C, stir and react at constant temperature for 4-5h, filter, extract and dry to obtain the acyl chloride product 1; add 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 3, then add the above acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution 4, slowly drop the mixed solution 4 into the mixed solution 3 in an ice-water bath at 0°C, after the dropwise addition is completed, raise the temperature to 40°C, react at constant temperature for 8-10h, and distill under reduced pressure to obtain an antioxidant;
[0032] Further, the amount ratio of the loaded product, DMF, and thionyl chloride is 22-24 g: 100 mL: 0.6-0.8 mol; the amount ratio of 5-hexen-1-ol, pyridine, triethylamine, and dimethyl sulfoxide is 15-20 g: 0.01-0.015 mol: 0.1 mol: 85-95 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide is 23-25 g: 120-130 mL; the amount ratio of the mixed solution 3 and the mixed solution 4 is 90-100 mL: 125-135 mL;
[0033] During the reaction of step B4, the carboxyl groups on the surface of the loaded product react with thionyl chloride to generate an acyl chloride product 1; the acyl chloride product 1 then reacts with the hydroxyl group of 5-hexene-1-ol to generate an antioxidant containing a terminal double bond.
[0034] Beneficial effects of the invention: The invention discloses an aging-resistant overhead cable, which comprises a conductor core, an insulating layer and a sheath layer from the inside to the outside; the insulating layer is made of cross-linked polyethylene, and the cross-linked polyethylene is made of raw materials such as low-density polyethylene, a cross-linking agent, an anti-tree aging agent and an antioxidant.
[0035] The synthesized anti-tree aging agent includes nano magnesium oxide, benzophenone structure, and terminal carbon-carbon double bond; the terminal carbon-carbon double bond makes the anti-tree aging agent have a cross-linkable site, which increases the compatibility and dispersibility of the anti-tree aging agent in the matrix; after the nano magnesium oxide is modified, its surface hydrophilicity and oleophobicity are improved, and it is not easy to agglomerate in the matrix, which not only improves the mechanical properties of the insulating layer material, but also slows down the aggregation of charges, slows down the accumulation of space charges, and improves the breakdown field strength, so that the cross-linked polyethylene has good insulation performance and good water tree resistance; after aromatic voltage stabilizers such as benzophenone are grafted with nanoparticles such as nano magnesium oxide, and cross-linked with the matrix through the terminal carbon-carbon double bond, it is not easy to migrate out, and benzophenone can absorb the energy of high-energy electrons and release it in the form of heat energy, reduce the impact of high-energy electrons on polyethylene chains, improve the ability of insulating materials to withstand voltage, increase the tree voltage, and inhibit the initiation and growth of electrical trees; therefore, the anti-tree aging agent is used to improve the mechanical properties, insulation properties and anti-tree aging properties of the cable.
[0036] The synthesized antioxidant is obtained by loading compound s on mesoporous silica, including terminal carbon-carbon double bonds, mesoporous silica, hindered phenol structure, thiophene ring and thioether group; the terminal carbon-carbon double bonds make the antioxidant have cross-linking sites, thereby increasing the compatibility and dispersibility of the antioxidant in the matrix; after loading compound s on mesoporous silica, the compound s is slowly released during the gradual aging process of the matrix, which can effectively inhibit its migration, so that the compound s reaches a very high concentration without blooming, and effectively improves the continuous antioxidant capacity of the insulating layer material; the hindered phenol structure generates hydroperoxides in the oxidative degradation reaction of the polymer, so that the oxidative degradation reaction is terminated, and the thioether group can reduce and decompose the hydroperoxides, and the hindered phenol structure and the thioether group produce rapid intramolecular synergistic effects to prevent the polymer oxidation reaction from continuing, and the thiophene ring can effectively absorb ultraviolet energy and convert it into low-energy heat energy, thereby reducing the damage of ultraviolet rays to the material; therefore, the addition of the antioxidant makes the cable insulation layer have a lasting antioxidant aging property. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Example 1: A tree aging resistance agent, the preparation of which comprises the following steps:
[0039] Step A1: Add nano magnesium oxide to toluene, ultrasonically disperse for 40 minutes, add erucic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110°C, reflux and stir for 48 hours, then centrifuge for 10 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain modified magnesium oxide; the dosage ratio of nano magnesium oxide, toluene, erucic acid and N, N'-dicyclohexyl diimide is 5g:120mL:10g:2g;
[0040] Step A2: Add modified magnesium oxide to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4 hours to obtain an epoxy product; in a nitrogen atmosphere, add 3-benzoylbenzoic acid and toluene to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8 hours, then heat to 110°C, stir for 1 hour to obtain a hydroxyl product; the amount ratio of modified magnesium oxide, dichloromethane and 3-chloroperoxybenzoic acid is 12g:180mL:0.5mol; the amount ratio of 3-benzoylbenzoic acid, toluene, pyridine and epoxy product is 25g:100mL:0.2mol:13g;
[0041] Step A3: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add the above acryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly drop the mixed solution b into the mixed solution a in an ice water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 8 hours, and distill under reduced pressure to obtain a tree aging resistant agent; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 14g:0.01mol:0.5mol:70mL; the amount ratio of acryloyl chloride and dimethyl sulfoxide is 4.5g:20mL; the amount ratio of the mixed solution a to the mixed solution b is 75mL:25mL.
[0042] Embodiment 2: A kind of anti-branch aging agent, its preparation comprises the following steps:
[0043] Step A1: Add nano magnesium oxide to toluene, ultrasonically disperse for 40 minutes, add erucic acid and N, N'-dicyclohexyl diimide under stirring, heat to 115°C, reflux and stir for 49 hours, then centrifuge for 13 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain modified magnesium oxide; the dosage ratio of nano magnesium oxide, toluene, erucic acid and N, N'-dicyclohexyl diimide is 6g:120mL:10g:2g;
[0044] Step A2: Add modified magnesium oxide to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4.5 hours to obtain an epoxy product; in a nitrogen atmosphere, add 3-benzoylbenzoic acid and toluene to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 9 hours, then heat to 115°C, stir for 1.5 hours to obtain a hydroxyl product; the amount ratio of modified magnesium oxide, dichloromethane and 3-chloroperoxybenzoic acid is 14g:185mL:0.8mol; the amount ratio of 3-benzoylbenzoic acid, toluene, pyridine and epoxy product is 28g:105mL:0.23mol:14g;
[0045] Step A3: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add the above acryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly drop the mixed solution b into the mixed solution a in an ice water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at constant temperature for 9 hours, and distill under reduced pressure to obtain a tree aging resistant agent; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 15g:0.013mol:0.8mol:75mL; the amount ratio of acryloyl chloride and dimethyl sulfoxide is 4.9g:25mL; the amount ratio of the mixed solution a to the mixed solution b is 80mL:30mL.
[0046] Embodiment 3: A kind of anti-branch aging agent, its preparation comprises the following steps:
[0047] Step A1: Add nano-magnesium oxide to toluene, ultrasonically disperse for 40 minutes, add erucic acid and N, N'-dicyclohexyl diimide under stirring, heat to 120°C, reflux and stir for 51 hours, then centrifuge for 15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain modified magnesium oxide; the dosage ratio of nano-magnesium oxide, toluene, erucic acid and N, N'-dicyclohexyl diimide is 7g:120mL:10g:2g;
[0048] Step A2: Add modified magnesium oxide to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 5 hours to obtain an epoxy product; in a nitrogen atmosphere, add 3-benzoylbenzoic acid and toluene to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 10 hours, then heat to 120°C, stir for 2 hours to obtain a hydroxyl product; the amount ratio of modified magnesium oxide, dichloromethane and 3-chloroperoxybenzoic acid is 16g:190mL:1.0mol; the amount ratio of 3-benzoylbenzoic acid, toluene, pyridine and epoxy product is 30g:110mL:0.25mol:15g;
[0049] Step A3: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add the above acryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly drop the mixed solution b into the mixed solution a in an ice water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 10 hours, and distill under reduced pressure to obtain a tree aging resistant agent; the amount ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 16g:0.015mol:1.0mol:80mL; the amount ratio of acryloyl chloride and dimethyl sulfoxide is 5.4g:30mL; the amount ratio of the mixed solution a to the mixed solution b is 85mL:35mL.
[0050] Example 4: An antioxidant, the preparation of which comprises the following steps:
[0051] Step B1: In a nitrogen atmosphere, 5-methylthiothiophene-2-carboxaldehyde and acetic anhydride are added to a reaction bottle, reflux and stir, and the temperature is raised to 150°C, and potassium carbonate is added, and the reaction is stirred at constant temperature for 24 hours, and the unsaturated carboxylic acid is obtained by extraction, rotary evaporation, and drying; the unsaturated carboxylic acid is added to DMF, stirred, and thionyl chloride is slowly added, the temperature is raised to 40°C, and the reaction is stirred at constant temperature for 4 hours, and the acid chloride product is obtained by filtering, extraction, and drying; the dosage ratio of 5-methylthiothiophene-2-carboxaldehyde, acetic anhydride, and potassium carbonate is 0.1 mol: 0.05 mol: 5 mmol; the dosage ratio of unsaturated carboxylic acid, DMF, and thionyl chloride is 0.1 mol: 90 mL: 0.1 mol;
[0052] Step B2: 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the above-mentioned acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2, and the mixed solution 2 is slowly added dropwise to the mixed solution 1 in an ice-water bath at 0°C. After the addition is completed, the temperature is raised to 40°C, and the reaction is carried out at a constant temperature for 8 hours, and the compound s is obtained by distillation under reduced pressure; the amount ratio of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.01 mol: 0.1 mol: 80 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 100 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 85 mL: 105 mL;
[0053] Step B3: Compound S is added to acetone, and the mixture is stirred at room temperature for 15 minutes to obtain a mixed solution, and then carboxyl hollow mesoporous silica is added, and the mixture is stirred at room temperature for 2 hours, and then vacuumed for 30 minutes, and then allowed to flow to the atmosphere for 15 minutes. The steps of vacuuming and then passing through the atmosphere are repeated three times, and the loaded product is obtained after washing with ethanol and deionized water, drying and grinding; the dosage ratio of compound S, acetone, and carboxyl hollow mesoporous silica is 43g:430mL:20g;
[0054] Step B4: Add the loaded product to DMF, start stirring, slowly add dichlorothionyl, heat to 40°C, stir and react at constant temperature for 4h, filter, extract and dry to obtain the acyl chloride product 1; add 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 3, then add the above-mentioned acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution 4, slowly drop the mixed solution 4 into the mixed solution 3 under a 0°C ice water bath, after the dropwise addition is completed, heat to 40°C, react at constant temperature for 8h, and distill under reduced pressure to obtain an antioxidant; the amount ratio of the loaded product, DMF, and dichlorothionyl is 22g:100mL:0.6mol; the amount ratio of 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide is 15g:0.01mol:0.1mol l:85mL; the usage ratio of acyl chloride product 1 and dimethyl sulfoxide is 23g:120mL; the usage ratio of mixed solution 3 and mixed solution 4 is 90mL:125mL.
[0055] Example 5: An antioxidant, the preparation of which comprises the following steps:
[0056] Step B1: In a nitrogen atmosphere, 5-methylthiothiophene-2-carboxaldehyde and acetic anhydride are added to a reaction bottle, reflux and stir, and the temperature is raised to 160°C, and potassium carbonate is added, and the reaction is stirred at constant temperature for 25 hours, and the unsaturated carboxylic acid is obtained by extraction, rotary evaporation, and drying; the unsaturated carboxylic acid is added to DMF, stirring is started, and dithionyl chloride is slowly added, the temperature is raised to 45°C, and the reaction is stirred at constant temperature for 4.5 hours, and the acid chloride product is obtained by filtering, extraction, and drying; the dosage ratio of 5-methylthiothiophene-2-carboxaldehyde, acetic anhydride, and potassium carbonate is 0.1 mol: 0.06 mol: 6 mmol; the dosage ratio of unsaturated carboxylic acid, DMF, and dithionyl chloride is 0.1 mol: 90 mL: 0.13 mol;
[0057] Step B2: 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the above-mentioned acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2. In a 0°C ice-water bath, the mixed solution 2 is slowly added dropwise to the mixed solution 1. After the addition is completed, the temperature is raised to 40°C, and the reaction is carried out at a constant temperature for 9 hours. The compound s is obtained by distillation under reduced pressure; the amount ratio of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.013 mol: 0.1 mol: 85 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 105 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 90 mL: 110 mL;
[0058] Step B3: Compound S is added to acetone, and the mixture is stirred at room temperature for 15 minutes to obtain a mixed solution, and then carboxyl hollow mesoporous silica is added, and the mixture is stirred at room temperature for 2.3 hours, and then vacuumed for 30 minutes, and then allowed to flow to the atmosphere for 15 minutes. The steps of vacuuming and then passing through the atmosphere are repeated three times, and the loaded product is obtained after washing with ethanol and deionized water, drying and grinding; the dosage ratio of compound S, acetone, and carboxyl hollow mesoporous silica is 44g:440mL:23g;
[0059] Step B4: Add the loaded product to DMF, start stirring, slowly add dichlorothionyl, heat to 45°C, stir and react at constant temperature for 4.5h, filter, extract and dry to obtain the acyl chloride product 1; add 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 3, then add the above-mentioned acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution 4, slowly drop the mixed solution 4 into the mixed solution 3 under a 0°C ice water bath, after the dropwise addition is completed, heat to 40°C, react at constant temperature for 9h, and distill under reduced pressure to obtain an antioxidant; the amount ratio of the loaded product, DMF, and dichlorothionyl is 23g:100mL:0.7mol; the amount ratio of 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide is 18g:0.013mol:0.1mol l:90mL; the usage ratio of acyl chloride product 1 and dimethyl sulfoxide is 24g:125mL; the usage ratio of mixed solution 3 and mixed solution 4 is 95mL:130mL.
[0060] Example 6: An antioxidant, the preparation of which comprises the following steps:
[0061] Step B1: In a nitrogen atmosphere, 5-methylthiothiophene-2-carboxaldehyde and acetic anhydride are added to a reaction bottle, reflux and stir, and the temperature is raised to 170°C, and potassium carbonate is added, and the reaction is stirred at constant temperature for 26 hours, and the unsaturated carboxylic acid is obtained by extraction, rotary evaporation, and drying; the unsaturated carboxylic acid is added to DMF, stirred, and thionyl chloride is slowly added, the temperature is raised to 50°C, and the reaction is stirred at constant temperature for 5 hours, and the acid chloride product is obtained by filtering, extraction, and drying; the dosage ratio of 5-methylthiothiophene-2-carboxaldehyde, acetic anhydride, and potassium carbonate is 0.1 mol: 0.07 mol: 8 mmol; the dosage ratio of unsaturated carboxylic acid, DMF, and thionyl chloride is 0.1 mol: 90 mL: 0.15 mol;
[0062] Step B2: 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide are added to a flask to obtain a mixed solution 1, and then the above-mentioned acyl chloride product is added to dimethyl sulfoxide to obtain a mixed solution 2, and the mixed solution 2 is slowly added dropwise to the mixed solution 1 in an ice-water bath at 0°C. After the addition is completed, the temperature is raised to 40°C, and the reaction is carried out at a constant temperature for 10 hours, and the compound s is obtained by distillation under reduced pressure; the amount ratio of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.015 mol: 0.1 mol: 90 mL; the amount ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 110 mL; the amount ratio of the mixed solution 1 to the mixed solution 2 is 95 mL: 115 mL;
[0063] Step B3: Compound S is added to acetone, and the mixture is stirred at room temperature for 20 minutes to obtain a mixed solution, and then carboxyl hollow mesoporous silica is added, and the mixture is stirred at room temperature for 2.5 hours, and then vacuumed for 30 minutes, and then allowed to flow to the atmosphere for 15 minutes. The steps of vacuuming and then passing through the atmosphere are repeated three times, and the loaded product is obtained after washing with ethanol and deionized water, drying and grinding; the dosage ratio of compound S, acetone, and carboxyl hollow mesoporous silica is 45g:450mL:25g;
[0064] Step B4: Add the loaded product to DMF, start stirring, slowly add dichlorothionyl, heat to 50°C, stir and react at constant temperature for 5h, filter, extract and dry to obtain the acyl chloride product 1; add 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 3, then add the above-mentioned acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution 4, slowly drop the mixed solution 4 into the mixed solution 3 under a 0°C ice water bath, after the dropwise addition is completed, heat to 40°C, react at constant temperature for 10h, and distill under reduced pressure to obtain an antioxidant; the amount ratio of the loaded product, DMF and dichlorothionyl is 24g:100mL:0.8mol; the amount ratio of 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide is 20g:0.015mol:0.1mol l:95mL; the usage ratio of acyl chloride product 1 and dimethyl sulfoxide is 25g:130mL; the usage ratio of mixed solution 3 and mixed solution 4 is 100mL:135mL.
[0065] Embodiment 7: An aging-resistant overhead cable, comprising a conductor core, an insulation layer and a sheath layer from the inside out; the conductor core is formed by twisting 14 aluminum alloy wires, and the sheath layer is made of TPE sheath material; the insulation layer is made of cross-linked polyethylene, and the cross-linked polyethylene comprises the following raw materials in parts by weight: 170 parts of low-density polyethylene, 10 parts of a cross-linking agent, 8.5 parts of a tree aging resistance agent and 4 parts of an antioxidant; the cross-linking agent is benzoyl peroxide;
[0066] The preparation of the aging-resistant overhead cable comprises the following steps:
[0067] Step S1: low-density polyethylene is placed in a rheometer for melt blending, mixed at 105° C. and a rotation speed of 50 r / min for 4 minutes, and then the anti-tree aging agent and cross-linking agent obtained in Example 1 are added, and then mixed for 3 minutes, and then the antioxidant obtained in Example 4 is added, and finally mixed for 10 minutes to obtain cross-linked polyethylene;
[0068] Step S2: Twisting the aluminum alloy wires to form a conductor core, extruding and depositing the cross-linked polyethylene on the periphery of the conductor core using an extruder to form an insulating layer; then extruding and depositing the TPE sheath material on the periphery of the insulating layer to obtain a sheath layer, and annealing after extrusion to obtain an aging-resistant overhead cable.
[0069] Embodiment 8: An aging-resistant overhead cable, comprising a conductor core, an insulation layer and a sheath layer from the inside out; the conductor core is formed by twisting 16 aluminum alloy wires, and the sheath layer is made of TPE sheath material; the insulation layer is made of cross-linked polyethylene, and the cross-linked polyethylene comprises the following raw materials in parts by weight: 175 parts of low-density polyethylene, 11 parts of a cross-linking agent, 9.5 parts of a tree aging resistance agent and 5 parts of an antioxidant; the cross-linking agent is benzoyl peroxide;
[0070] The preparation of the aging-resistant overhead cable comprises the following steps:
[0071] Step S1: low-density polyethylene is placed in a rheometer for melt blending, mixed at 105° C. and a rotation speed of 50 r / min for 5 minutes, and then the anti-tree aging agent and cross-linking agent obtained in Example 2 are added, and then mixed for 3 minutes, and then the antioxidant obtained in Example 5 is added, and finally mixed for 13 minutes to obtain cross-linked polyethylene;
[0072] Step S2: Twisting the aluminum alloy wires to form a conductor core, extruding and depositing the cross-linked polyethylene on the periphery of the conductor core using an extruder to form an insulating layer; then extruding and depositing the TPE sheath material on the periphery of the insulating layer to obtain a sheath layer, and annealing after extrusion to obtain an aging-resistant overhead cable.
[0073] Embodiment 9: An aging-resistant overhead cable, comprising a conductor core, an insulation layer and a sheath layer from the inside out; the conductor core is formed by twisting 18 aluminum alloy wires, and the sheath layer is made of TPE sheath material; the insulation layer is made of cross-linked polyethylene, and the cross-linked polyethylene comprises the following raw materials by weight: 180 parts of low-density polyethylene, 12 parts of a cross-linking agent, 10.5 parts of a tree aging resistance agent and 6 parts of an antioxidant; the cross-linking agent is benzoyl peroxide;
[0074] The preparation of the aging-resistant overhead cable comprises the following steps:
[0075] Step S1: low-density polyethylene is placed in a rheometer for melt blending, and after mixing for 6 minutes at 110° C. and a rotation speed of 50 r / min, the anti-tree aging agent and the cross-linking agent obtained in Example 3 are added, and after mixing for another 3 minutes, the antioxidant obtained in Example 6 is added, and finally mixing for 15 minutes to obtain cross-linked polyethylene;
[0076] Step S2: Twisting the aluminum alloy wires to form a conductor core, extruding and depositing the cross-linked polyethylene on the periphery of the conductor core using an extruder to form an insulating layer; then extruding and depositing the TPE sheath material on the periphery of the insulating layer to obtain a sheath layer, and annealing after extrusion to obtain an aging-resistant overhead cable.
[0077] Comparative Example 1: This comparative example is a commercially available aging-resistant overhead cable, whose insulation layer is made of ordinary cross-linked polyethylene material.
[0078] Comparative Example 2: Compared with Example 9, the anti-tree aging agent is replaced with anti-tree aging agent d, and the rest is exactly the same as Example 9 to prepare an aging-resistant overhead cable; the preparation process of anti-tree aging agent d is: the 3-benzoylbenzoic acid in step A2 in Example 3 is replaced with acrylic acid, that is, the benzophenone structure is not introduced, and then the anti-tree aging agent d is prepared according to the reaction steps of Example 3.
[0079] Comparative Example 3: Compared with Example 9, the antioxidant is replaced by the compound s obtained in Example 6, that is, no mesoporous silica is used, and the rest is exactly the same as in Example 9 to prepare an aging-resistant overhead cable.
[0080] The aging-resistant overhead cable prepared by the present invention is further tested for its effect, and the test results are as follows.
[0081] In order to test the aging-resistant overhead cable prepared by the present invention, the mechanical properties (tensile strength and elongation at break) of the insulation layer were tested according to GB / T2951-2008 "General Test Methods for Insulation and Sheath Materials of Electric and Optical Cables", and the results are recorded in Table 1;
[0082] The test method for the average AC breakdown field strength and the average DC breakdown field strength in Table 1 is: apply a linearly increasing AC high voltage or DC high voltage to 100 μm film samples of the insulating layer materials of the cables in Examples 7-9 and Comparative Examples 1-3 at room temperature until the samples break down. According to the method of GB / T11017.1-2014 "Rated voltage 110 kV cross-linked polyethylene insulated power cable and its accessories", the average AC breakdown field strength and the average DC breakdown field strength of 10 samples are obtained respectively, and the results are recorded in Table 1.
[0083] The average electrical tree initiation voltage test method in Table 1 is: the electrical tree initiation voltage test of the insulation layer materials of the cables in Examples 7-9 and Comparative Examples 1-3 is carried out at room temperature using a needle-plate electrode structure, the needle-plate distance is 3 mm, the needle tip curvature radius is 5 μm, the boost mode is linear boost, and the average electrical tree initiation voltage of 10 samples is obtained according to the method of GB / T11017.1-2014 "Rated voltage 110 kV cross-linked polyethylene insulated power cable and its accessories", and the results are recorded in Table 1.
[0084] The aging method in Table 1 is: the insulation layer materials of the cables in Examples 7-9 and Comparative Examples 1-3 are placed in an ultraviolet light with an intensity of 0.89 W / m 2 The samples were aged at 50 °C for 30 days, and the tensile strength retention rate and elongation at break retention rate were determined according to the method of GB / T2951-2008. The results are recorded in Table 1.
[0085] Table 1: Test results
[0086]
[0087] According to the data in Table 1, it can be seen from the comparison between Examples 7-9 and Comparative Example 1 that the insulation layer of the aging-resistant overhead cable prepared by the present invention has good mechanical properties, tree aging resistance, insulation performance, and oxidation aging resistance, so that the mechanical properties and aging resistance of the cable are excellent, and the service life is extended. It can be seen from the comparison between Example 9 and Comparative Example 2 that the use of tree aging resistance agent and the introduction of benzophenone structure can improve the voltage resistance of the insulation layer of the overhead cable, effectively inhibit the growth of electrical tree branches, and help improve the tree aging resistance of the cable. It can be seen from the comparison between Example 9 and Comparative Example 3 that the use of antioxidants and the use of mesoporous silica to load compound s, compound s is not easy to migrate and can be slowly released, which is more conducive to the improvement of the continuous oxidation aging resistance of the insulation layer, thereby helping to improve the oxidation aging resistance of the cable.
[0088] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. An aging-resistant overhead cable, characterized in that: From the inside to the outside, it includes a conductor core, an insulating layer and a sheath layer; the insulating layer is made of cross-linked polyethylene, and the cross-linked polyethylene includes the following raw materials by weight: 170-180 parts of low-density polyethylene, 10-12 parts of a cross-linking agent, 8.5-10.5 parts of a tree aging resistance agent, and 4-6 parts of an antioxidant; The preparation of the anti-branching agent comprises the following steps: Step A1: Add nano magnesium oxide to toluene, ultrasonically disperse for 40 minutes, add erucic acid and N, N'-dicyclohexyl diimide under stirring, heat to 110-120°C, reflux and stir for 48-51 hours, then centrifuge for 10-15 minutes, centrifuge the lower precipitate with anhydrous ethanol, and finally vacuum dry the lower precipitate at 80°C for 12 hours to obtain modified magnesium oxide; Step A2: Add modified magnesium oxide to dichloromethane, start stirring, then add 3-chloroperoxybenzoic acid, stir and react at room temperature for 4-5 hours to obtain an epoxy product; in a nitrogen atmosphere, add 3-benzoylbenzoic acid and toluene to a flask, heat to 45°C, add pyridine, start stirring, add the epoxy product to the flask, stir and react for 8-10 hours, then heat to 110-120°C, stir for 1-2 hours to obtain a hydroxyl product; Step A3: Add the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution a, then add the above-mentioned acryloyl chloride into dimethyl sulfoxide to obtain a mixed solution b, slowly drop the mixed solution b into the mixed solution a in an ice water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain a tree aging resistant agent.
2. The aging-resistant overhead cable according to claim 1, characterized in that: In step A1, the usage ratio of nano-magnesium oxide, toluene, erucic acid and N,N'-dicyclohexyldiimide is 5-7g:120mL:10g:2g.
3. The aging-resistant overhead cable according to claim 1, characterized in that: In step A2, the usage ratio of modified magnesium oxide, dichloromethane and 3-chloroperoxybenzoic acid is 12-16 g: 180-190 mL: 0.5-1.0 mol; the usage ratio of 3-benzoylbenzoic acid, toluene, pyridine and epoxy product is 25-30 g: 100-110 mL: 0.2-0.25 mol: 13-15 g.
4. The aging-resistant overhead cable according to claim 1, characterized in that: In step A3, the usage ratio of the hydroxyl product, pyridine, triethylamine and dimethyl sulfoxide is 14-16 g: 0.01-0.015 mol: 0.5-1.0mol:70-80mL; the usage ratio of acryloyl chloride and dimethyl sulfoxide is 4.5-5.4g:20-30mL; the usage ratio of mixed solution a and mixed solution b is 75-85mL:25-35mL.
5. The aging-resistant overhead cable according to claim 1, characterized in that: The preparation of the antioxidant comprises the following steps: Step B1: In a nitrogen atmosphere, 5-methylthiothiophene-2-carboxaldehyde and acetic anhydride are added to a reaction bottle, refluxed and stirred, and the temperature is raised to 150-170°C, and potassium carbonate is added, and the reaction is stirred at constant temperature for 24-26 hours, and the unsaturated carboxylic acid is extracted, rotary evaporated, and dried to obtain an unsaturated carboxylic acid; the unsaturated carboxylic acid is added to DMF, stirred, and thionyl chloride is slowly added, the temperature is raised to 40-50°C, and the reaction is stirred at constant temperature for 4-5 hours, and the acyl chloride product is obtained by filtering, extracting, and drying; Step B2: Add 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide into a flask to obtain a mixed solution 1, then add the above-mentioned acyl chloride product into dimethyl sulfoxide to obtain a mixed solution 2, slowly dropwise add the mixed solution 2 into the mixed solution 1 in an ice-water bath at 0°C, after the dropwise addition is completed, heat to 40°C, react at a constant temperature for 8-10 hours, and distill under reduced pressure to obtain compound s; Step B3: Compound s is added to acetone, and the mixture is stirred at room temperature for 10-20 minutes to obtain a mixed solution, and then carboxyl hollow mesoporous silica is added, and the mixture is stirred at room temperature for 2-2.5 hours, and then vacuumed for 30 minutes, and then allowed to flow to the atmosphere for 15 minutes. The steps of vacuuming and then allowing to flow to the atmosphere are repeated three times, and the loaded product is obtained after washing with ethanol and deionized water, drying and grinding; Step B4: Add the loaded product to DMF, start stirring, slowly add dichlorothionyl, raise the temperature to 40-50°C, stir and react at constant temperature for 4-5h, filter, extract and dry to obtain the acyl chloride product 1; add 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide to a flask to obtain a mixed solution 3, then add the above-mentioned acyl chloride product 1 to dimethyl sulfoxide to obtain a mixed solution 4, slowly drop the mixed solution 4 into the mixed solution 3 in an ice-water bath at 0°C, after the dropwise addition is completed, raise the temperature to 40°C, react at constant temperature for 8-10h, and distill under reduced pressure to obtain an antioxidant.
6. The aging-resistant overhead cable according to claim 5, characterized in that: In step B1, the usage ratio of 5-methylthiothiophene-2-carboxaldehyde, acetic anhydride and potassium carbonate is 0.1 mol: 0.05-0.07 mol: 5-8 mmol; the usage ratio of unsaturated carboxylic acid, DMF and dichlorothionyl is 0.1 mol: 90 mL: 0.1-0.15 mol; in step B3, the usage ratio of compound S, acetone and carboxyl hollow mesoporous silica is 43-45 g: 430-450 mL: 20-25 g.
7. The aging-resistant overhead cable according to claim 5, characterized in that: In step B2, the usage ratio of 3,5-di-tert-butyl-4-hydroxybenzyl alcohol, pyridine, triethylamine and dimethyl sulfoxide is 0.1 mol: 0.01-0.015 mol: 0.1 mol: 80-90 mL; the usage ratio of the acyl chloride product and dimethyl sulfoxide is 0.1 mol: 100-110 mL; the usage ratio of mixed solution 1 and mixed solution 2 is 85-95 mL: 105-115 mL.
8. The aging-resistant overhead cable according to claim 5, characterized in that: In step B4, the amount ratio of the loaded product, DMF, and dichlorothionyl is 22-24 g: 100 mL: 0.6-0.8 mol; the amount ratio of 5-hexen-1-ol, pyridine, triethylamine and dimethyl sulfoxide is 15-20 g: 0.01-0.015 mol: 0.1 mol: 85-95 mL; the amount ratio of the acyl chloride product 1 and dimethyl sulfoxide is 23-25 g: 120-130 mL; the amount ratio of the mixed solution 3 and the mixed solution 4 is 90-100 mL: 125-135 mL.
9. The aging-resistant overhead cable according to claim 1, characterized in that: The conductor core is formed by twisting a plurality of aluminum alloy wires, the sheath layer is made of TPE sheath material, and the cross-linking agent is benzoyl peroxide.
10. The production process of an aging-resistant overhead cable according to claim 1, characterized in that: The steps include: Step S1: low-density polyethylene is placed in a rheometer for melt blending, mixed at 105-110° C. and a rotation speed of 50 r / min for 4-6 minutes, then an anti-tree aging agent and a cross-linking agent are added, mixed for another 3 minutes, an antioxidant is added, and finally mixed for 10-15 minutes to obtain cross-linked polyethylene; Step S2: Twisting the aluminum alloy wires to form a conductor core, extruding and depositing the cross-linked polyethylene on the periphery of the conductor core using an extruder to form an insulating layer; then extruding and depositing the TPE sheath material on the periphery of the insulating layer to obtain a sheath layer, and annealing after extrusion to obtain an aging-resistant overhead cable.
Citation Information
Patent Citations
Crosslinked polyethylene power cable with electrical tree aging preventive function
CN106531316A
Anti-aging photovoltaic cable and preparation method thereof
CN116478488A
Anti-aging power cable
CN118580625A
Crosslinked polyethylene insulated middle-high voltage power cable and preparation method thereof
CN118737523A
Halogen-free heat aging-resistant flame-retardant resin compound and wire and cable using the same
US20140141241A1
